Standing Authentic Evidence Which Application Made By Notary-PPAT Of Uitvoerbaar Bij Voorraad (Ruling That Can Run Over First) - Saddam Hussein; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
This study aims to determine the extent of the Status Evidence Authentic Notary or PPAT made towards the implementation of Voerbaar Uit Voorraad Bij (The decision to run first) in the District Court of Class IA Kendari. This study uses normative juridical approach, where data is collected through the study of literature materials and interviews and then analyzed by qualitative descriptive method is an argument of a logical and systematic law in accordance with the formulation of the problem has been formulated.From the results of the research it is concluded that from the point of view of the Law of Evidence in the world of Justice in Indonesia that the Position of Authentic Evidence made by a Notary or PPAT is the same / equivalent to other Authentic Evidence made by other authorized officials such as BPN, Camat, Bailiff, etc., as well as Decisions that can be implemented in advance (uitvoerbaar bij voorraad) and decisions that have permanent strength still experience obstacles in their implementation. These obstacles are caused by both juridical and non-juridical factors. Decisions that can be implemented first (uitvoerbaar bij voorraad) are still very rare, practiced in district courts, especially the Klas IA Kendari district court, that based on our research results, data is obtained that within a period of 4 years, from January 2016 to December 2019 The Kendari District Court has only 1 (one) decision regarding the uitvoerbaar bij voorraad. The obstacles experienced by judges in the District Court, especially the Kendari District Court, are due to the tight supervision of the High Court and the Supreme Court. Because in order to carry out a decision that can be implemented in advance (uitvoerbaar bij voorraad), it must obtain approval from the High Court, and even the High Court before allowing the implementation of the decision or execution, sometimes asking for consideration from the Supreme Court. This is the cause of the Judges' reluctance to issue a verdict that can be implemented first (uitvoerbaar bij voorraad).